Analysis of Chinese Market Average Daily Rate (ADR) to Overall ADR at Conrad Bali Hotel - Ni Kadek Sri Jayanti; I Ketut Budarma; I Wayan Jendra (Politeknik Negeri Bali, 2020)
This study aims to analyze the relationship and influence of the Chinese market Average Daily Rate (ADR) on the overall ADR at Conrad Bali Hotel. Data collection used in this study through observation, interview, and documentation. The analysis techniques used are descriptive statistics, correlation analysis, simple linear regression, and the coefficient of determination test (R2). The results of this study indicated that the Chinese market ADR (X) variable has a positive correlation with very strong category, overall ADR with a correlation value of 0.819. The coefficient regression is 1.085 and the coefficient determination shows that the influence of Chinese market ADR (X) on overall ADR (Y) is 66%. Thus, Chinese market can be an option to filling the occupancy when low seasons and a good target market when special occasion but should be followed by a necessary way to optimize its strength.